2012
DOI: 10.4081/ejh.2012.20
|View full text |Cite
|
Sign up to set email alerts
|

Diaminobenzidine photoconversion is a suitable tool for tracking the intracellular location of fluorescently labelled nanoparticles at transmission electron microscopy

Abstract: Chitosan-based nanoparticles (NPs) deserve particular attention as suitable drug carriers in the field of pharmaceutics, since they are able to protect the encapsulated drugs and/or improve their efficacy by making them able to cross biological barriers (such as the blood-brain barrier) and reach their intracellular target sites. Understanding the intracellular location of NPs is crucial for designing drug delivery strategies. In this study, fluorescently-labelled chitosan NPs were administered in vitro to a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 40 publications
3
55
0
Order By: Relevance
“…Now, we aimed at depicting the molecular events leading to HMA cytotoxicity. First, we exploited the fluorescent properties of HMA [7] using the diaminobenzidine (DAB) photo-oxidation technique, which is based on the formation of an electron-dense osmiophilic product that precipitates in close proximity to the fluorophore, thereby allowing its ultrastructural detection [15, 19]. Electron microscopy analysis of HMA-treated HCT-116 colon carcinoma cells revealed electron-dense black spots within the cytoplasm, enclosed within vesicles (red*), which are present only as an effect of HMA, given that in untreated cells no evidence of roundish deposit of electron-dense products was found (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, we aimed at depicting the molecular events leading to HMA cytotoxicity. First, we exploited the fluorescent properties of HMA [7] using the diaminobenzidine (DAB) photo-oxidation technique, which is based on the formation of an electron-dense osmiophilic product that precipitates in close proximity to the fluorophore, thereby allowing its ultrastructural detection [15, 19]. Electron microscopy analysis of HMA-treated HCT-116 colon carcinoma cells revealed electron-dense black spots within the cytoplasm, enclosed within vesicles (red*), which are present only as an effect of HMA, given that in untreated cells no evidence of roundish deposit of electron-dense products was found (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were finally examined and photographed with a Zeiss EM 900 electron microscope at 80 KV (Carl Zeiss, Jena, Germany). The micrographs were then developed and digitalised [15]. …”
Section: Methodsmentioning
confidence: 99%
“…TEM images showed that labeled ASCs incorporate USPIO by endocytic mechanisms, as already reported. 29 It has been demonstrated that nanoparticles internalized by endocytosis often accumulate inside multivesicular bodies, 30 which, in turn, may fuse with the plasma membrane thus releasing their cargo (exosomes). 31 It is likely that USPIO undergo the same secretion process of the endosomal system.…”
Section: Discussionmentioning
confidence: 99%
“…However, their low water solubility often leads to decreased transfection efficiency [9,10]. To overcome this problem, chitosan nanoparticles have been linked to different molecules to increase their solubility.…”
Section: Drug and Genetic Materials Delivery To The Cnsmentioning
confidence: 99%